2001
DOI: 10.1161/hy1101.099502
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Ramipril on Ambulatory and Office Blood Pressures

Abstract: Abstract-In the HOPE-trial, the ACE inhibitor ramipril significantly reduced cardiovascular morbidity and mortality in patients at high risk for cardiovascular events. The benefit could only partly be attributed to the modest mean reduction of office blood pressure (OBP) during the study period (3/2 mm Hg). However, because according to the HOPE protocol ramipril was given once daily at bedtime and blood pressure was measured during the day, the 24-hour reduction of blood pressure may be underestimated based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
254
1
12

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(277 citation statements)
references
References 20 publications
10
254
1
12
Order By: Relevance
“…Although our data are clear-cut, they do not necessarily obviate the results of well-designed prospective clinical trials demonstrating beneficial effects of ACE inhibitors or ARBs on regression of LVH (29,30). Rather, they suggest that the benefits of these agents in LVH are not a consequence of blocking cellular actions of Ang II in the heart, but may be due to differences in the degree or pattern of blood pressure control that was achieved (56).…”
Section: Discussioncontrasting
confidence: 59%
“…Although our data are clear-cut, they do not necessarily obviate the results of well-designed prospective clinical trials demonstrating beneficial effects of ACE inhibitors or ARBs on regression of LVH (29,30). Rather, they suggest that the benefits of these agents in LVH are not a consequence of blocking cellular actions of Ang II in the heart, but may be due to differences in the degree or pattern of blood pressure control that was achieved (56).…”
Section: Discussioncontrasting
confidence: 59%
“…44 This may partly be explained by a marked reduction in nocturnal BP (À17/À8 mm Hg), as shown in a small ABPM substudy of HOPE (mean age, 71 years; n¼38), 45 as well as by data showing that bedtime administration of ramipril could reduce nocturnal BP more efficiently than morning administration of ramipril. 46 Other evidence provided by the BP-lowering arm of the ABPM substudy of the Anglo-Scandinavian cardiac outcomes trial (mean age, 63 years; n¼1905) showed a more significant reduction of nocturnal BP with an amlodipine-perindopril regimen than with atenololthiazide, despite the fact that the daytime BP was higher in the former group, which might account for the lower cardiovascular events in the amlodipine-perindopril group.…”
Section: Treatment Of Nocturnal Bp Increasesmentioning
confidence: 99%
“…Till date, two large prospective randomized control trials have implemented nighttime administration of 51 ramipril was administered once daily at bedtime and resulted in an outstanding benefit on CV morbidity and mortality in high-vascular-risk subjects. In a small substudy of the HOPE trial, 52 in patients with peripheral arterial disease, 24-h systolic and diastolic BP levels were significantly reduced by 10 and 4 mm Hg, respectively, mainly because of a more pronounced systolic and diastolic BP-lowering effect during nighttime (that is, 17 and 8 mm Hg, respectively). The night-to-day ratio was also significantly decreased in the ramipril group.…”
Section: Chronotherapy and Other Interventions For Nighttime Bpmentioning
confidence: 99%